2000
DOI: 10.1111/1467-9914.00123
|View full text |Cite
|
Sign up to set email alerts
|

Employment Decisions of Married Women: Evidence and Explanations

Abstract: Aggregate evidence has revealed a significant increase in women's labour market participation (especially among married women) and a decline in male participation, both in Italy and in all the other OECD countries. This paper empirically tests the relationship between the education and employment status of husbands and wives using the Bank of Italy Survey (1995). The results of our analysis show that employed women are likely to be married to employed men with a higher level of education and higher income. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Our analysis of other individual-level characteristics showed that 90% of the urban Kenyan women were married to men with similar or higher education levels, a finding consistent with previous studies conducted in Central Asia and the Middle East 54 . Further, our bivariate and multivariate analyses indicate that couples where both partners had more than a primary education were more likely to use contraception compared to couples with only primary education.…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis of other individual-level characteristics showed that 90% of the urban Kenyan women were married to men with similar or higher education levels, a finding consistent with previous studies conducted in Central Asia and the Middle East 54 . Further, our bivariate and multivariate analyses indicate that couples where both partners had more than a primary education were more likely to use contraception compared to couples with only primary education.…”
Section: Discussionsupporting
confidence: 90%
“… As for the individual controls, they enter with a similar sign and statistical significance to that found in the previous literature. See, for instance, Dalmazzo and de Blasio (2007) and Colussi (1997) on worker productivity; Barca and Cannari (1997) and Alesina et al (2001) on entrepreneurship; del Boca, Biey, and Silvia (2000) on female participation. …”
mentioning
confidence: 99%
“…We now consider the occupational status of the mother. On one hand this variable can be expected to have a positive effect as mother's work increasing family resources can subsidize children in their choice of living independently (Diaz and Guillo, 2005; McElroy, 1985) and could have a ‘cultural impact’ on children's desire for independence (Del Boca et al ., 2000; Fernandez et al ., 2005; Giuliano, 2007). On the other hand, mother's additional income can be also used to supply larger space and support in the parental house for children prolonging their co‐residence.…”
Section: Resultsmentioning
confidence: 99%
“…Mother's working status can also be interpreted as a proxy for the family attitude towards women's independence. Growing up in a household with positive attitudes towards women's working may contribute to develop children's desire of independence (Del Boca et al ., 2000; Farrè and Vella, 2007; Fernandez et al ., 2005).…”
Section: What Determines Different Living Arrangements?mentioning
confidence: 99%